Exploring the impact of body-worn video on the everyday behaviours of police officers. (June 2022) - Harrison, Karen; L'Hoiry, Xavier; Santorso, Simone
The use of body-worn video in Police Forces in England and Wales is not new. On the whole, evaluations have been positive, although, there is little evidence regarding how beneficial the cameras can be in terms of how they impact on the everyday behaviours of police officers. This article looks at how the implementation of BWV into one police force in England impacted on the behaviour of those officers who wore the technology. While the dominant view is positive, concerns as to privacy infringements and the use of BWV footage as a potential tool for supervisory surveillance emerged.